Hyaluronidase-Assisted Resuscitation in Kenya for Severely Dehydrated Children. Issue 10 (October 2019) - Zubairi, Hijab; Nelson, Brett D.; Tulshian, Priyanka; Fredricks, Karla; Altawil, Zaid; Mireles, Sarah; Odongo, Fred; Burke, Thomas F.
Abstract : Background: Dehydration, mainly due to diarrheal illnesses, is a leading cause of childhood mortality worldwide. Intravenous (IV) therapy is the standard of care for patients who were unable to tolerate oral rehydration; however, placing IVs in fragile, dehydrated veins can be challenging. Studies in resource-rich settings comparing hyaluronidase-assisted subcutaneous rehydration with standard IV rehydration in children have demonstrated several benefits of subcutaneous rehydration, including time and success of line placement, ease of use, satisfaction, and cost-effectiveness. Methods: A single-arm trial assessing the feasibility of hyaluronidase-assisted subcutaneous resuscitation for the treatment of moderately to severely dehydrated individuals in western Kenya was conducted. Children aged 2 months or older who presented with moderately to severely dehydration clinically warranting parenteral rehydration and had at least 2 failed IV attempts were eligible. Study staff received training on standard dehydration management and hyaluronidase infusion processes. Children received all other standards of care. They were monitored from presentation and through discharge, with a 1-week phone follow-up. Predischarge surveys were completed by caregivers, and semistructured interviews with providers were performed. Results: A total of 51 children were enrolled (median age, 13.0 months; interquartile range of 18 months). Fifty-one patients (100%) had severe dehydration. The median length of subcutaneous infusion was 3.0 hours (interquartile range [IQR], 2.95). The median total subcutaneous infusion was 700.0 mL (IQR, 420 mL). Median time to resolution of moderate to severe dehydration symptoms was 3.0 hours (IQR, 2.95 hours). There were no significant complications. Conclusions: Hyaluronidase-assisted subcutaneous resuscitation is a feasible alternative to IV hydration in moderately to severely dehydrated children with difficult to obtain IV access in resource-limited areas. Abstract : Supplemental digital content is available in the text.